ANALISIS EFEKTIVITAS PERIKLANAN KEK PISANG VILLA MELALUI IKLAN BILLBOARD DAN VIDEOTRON DENGAN MENGGUNAKAN EPIC MODEL - Lisa Wardi; Dwi Kartikasari (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract: This study aims to determine the effectiveness of advertising bill- board and videotron conductedby PT Indonesia Villajaya. The technique of collecting data using interviews, documentation and questionnaires. Methods of  data  analysis  used  in  this  study  views  from  four  dimensions  EPIC  ie Empathy, Persuasion, Impact and Communication.  Results the showed that (1) the design of advertising conducted by PT Indonesia Villajaya overall prefer the products they sell and every word and sentence in the ad uses simple words that is easily understood by the consumer (2) advertising billboard and video- tron used by PT Indonesia Villajaya been effective (3) on aadvertising bill- board the most effective dimension is empathy and the dimensions of the ad videotron is most effective impact (4) billboard advertising is more effective than advertising videotron. The implications of these results for the company to determine the effectiveness of advertising that has been done mainly on advertising billboard and videotron. With this research to know whether the purpose of advertising can be achieved and done well. Keywords : Empathy, Communication, Impact, Persuasion